MicroRNA-148a-3p is a candidate mediator of increased bone marrow adiposity and bone loss following spinal cord injury - Lincoln, Samantha; Morse, Leslie R.; Troy, Karen; Mattson, Nicole; Nguyen, Nguyen; Battaglino, Ricardo A. (Frontiers in Endocrinology, 2022)
Spinal cord injury is often followed by osteoporosis characterized by rapid and severe bone loss. This leads to an increased risk of osteoporotic fracture in people with spinal cord injury, resulting in increased healthcare costs, morbidity, and mortality. Though it is common, the mechanisms underlying this osteoporosis are not completely understood and treatment options are limited. No biomarkers have been identified for predicting fracture risk. In this study, we sought to investigate microRNA mediated mechanisms relating to osteoporosis following spinal cord injury. We studied subjects with acute SCI (n=12), chronic SCI (n=18), and controls with no SCI (n=23). Plasma samples from all subjects underwent transcriptomic analysis to quantify microRNA expression, after which miR-148a-3p was selected for further study. We performed CT scans of the knee on all subjects with SCI and analyzed these scans to quantify bone marrow adipose tissue volume. MiR-148a-3p was upregulated in subjects with acute SCI vs chronic SCI, as well as in acute SCI vs no SCI. Subjects with chronic SCI had greater levels of marrow adiposity in the distal femoral diaphysis compared to subjects with acute SCI. MiR-148a-3p levels were negatively associated with distal femoral diaphysis marrow adiposity. A multivariable model showed that miR-148a-3p and BMI explained 24% of variation in marrow adiposity. A literature search revealed that miR-148a-3p has multiple bone and fat metabolism related targets. Our findings suggest that miR-148a-3p is a mediator of osteoporosis following spinal cord injury and a potential future therapeutic target.